Pelvic floor muscle training in women with urinary incontinence and pelvic organ prolapse: A protocol study. - Maria Letícia A S de Carvalho; Lívia Oliveira Bezerra; Joyce Maria Pereira Oliveira; Maria Clara Eugênia Oliveira; Maria T A B C Micussi (PLoS ONE)
Objective To evaluate the effectiveness of pelvic floor muscle training (PFMT) on pelvic floor muscle (PFM) function and quality of life (QoL) in women with stress urinary incontinence (SUI) and pelvic organ prolapse (POP). Methods This study will be a randomized, controlled, parallel, and blinded clinical trial. The final sample will consist of 32 women diagnosed with SUI and cystocele (stage I and II). All volunteers will be assessed and reassessed using the same protocol: assessment form, gynecological examination, functional evaluation of PFM, and questionnaires to assess quality of life, urinary function, and sexual function. All volunteers will be evaluated for satisfaction levels post-treatment. The intervention will be PFMT, totaling 16 sessions to be conducted twice a week. Reevaluation will take place at the end of treatment and 1 month after completion of PFMT. Descriptive analysis and repeated measures ANOVA will be used for result analysis. A significance level of p<0.05 will be considered for all statistical tests. Ethics and dissemination This study has been submitted to the Ethics in Research Committee of the Federal University of Rio Grande do Norte and approved under protocol number 5.826.563. It has been registered with the Brazilian Clinical Trials Registry ReBec (RBR-49p6g3t). It is expected that these studies will provide a deeper understanding of the efficacy of PFMT in women with SUI and cystocele. Additionally, it aims to provide more insights into the efficacy of PFMT prior to surgery.